Case reportCoexistence of Sweet’s syndrome with hepatitis C – case report - Lesiak, Aleksandra; Chruściel, Anna; Sysa-Jędrzejowska, Anna; Narbutt, Joanna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Sweet’s syndrome is acute febrile neutrophilic dermatosis, which more frequently appears in women. It is characterized by the sudden onset of tender, red-to-purple infiltrative papules, and nodules which are typically accompanied by fever and peripheral neutrophilia. Skin lesions usually occur on the trunk, upper extremities and face. Sweet syndrome in some cases is treated as a paraneoplastic syndrome as it may be associated with lymphoproliferative disorders. We present a case of Sweet syndrome associated with hepatitis C. A 34-year old man was admitted to the Department of Dermatology because of a crop of erythematous and infiltrative skin lesions located mainly on the forehead, trunk, and upper and lower extremities, lasting for two days. Skin lesions were accompanied by malaise, fever, muscle and joint pains. Laboratory tests showed leukocytosis, neutrophilia, increased CRP and ESR, increase hepatic enzyme values and the presence of anti-HCV antibodies. In USG examination of the abdominal cavity slight hepatomegaly was observed. Based on clinical and histological findings a diagnosis of Sweet’s syndrome was established. All skin lesions and general symptoms improved after administration of systemic glucocorticosteroids. In USG examination of the abdominal cavity slight. Because of hepatic abnormalities the patient was next referred to the Department of Liver Disorders, where he is still being followed up. In the presented case we report rare coexistence of Sweet’s syndrome with hepatitis C, which indicates the necessity of viral analysis among patients with this entity.